Lead sulfide quantum dot photoelectric device and preparation method thereof
By using a three-layer hole transport modification layer in lead sulfide quantum dot optoelectronic devices, the interface contact and stability are improved, and the problem of low interface contact and working stability in the prior art is solved, achieving high efficiency and long-term Optoelectronic devices with lifespan.
Patent Information
- Application Number
- CN202411411496.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The interface contact and working stability of existing lead sulfide quantum dot optoelectronic devices is low, resulting in reduced device performance and shortened service life.
The hole transport modification layer adopts a three-layer structure, including the lower interface modification layer, the P-type organic polymer layer and the upper interface modification layer, is doped by poly[double( 4-phenyl)(2,4,6-trimethylphenyl)amine] layer to improve interface contact and stability.
It significantly improves the photoelectric conversion efficiency and working stability of lead sulfide quantum dot optoelectronic devices, extends the service life of the device, and reduces production costs.
Smart Images

Figure CN119486448A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lead sulfide quantum dot photoelectric device and a preparation method thereof, belonging to the technical field of solar photovoltaics. Background Art
[0002] Solar cells have a research history of nearly 70 years. Based on the increasingly mature technology of single-junction solar cells, stacked cells have also developed rapidly in recent years. They can combine multiple solar cells to achieve full coverage of the solar spectrum, thereby achieving a photoelectric conversion efficiency far exceeding that of single-junction solar cells. Among them, lead sulfide quantum dots, as a typical strong quantum confinement effect material, have received extensive attention in both basic research and applied research. Due to its narrow band gap (0.41 eV), the band gap of PbS quantum dots can be made to cover the near-infrared to short-wave infrared bands through size control, and it can be processed at low cost by solution method, which is a relatively ideal new infrared semiconductor material. The recently developed quantum dot semiconductor ink preparation technology can greatly reduce the material preparation cost and simplify the device preparation process, so that the optoelectronic application of PbS quantum dots has moved from the laboratory to industrialization, showing great application potential.
[0003] As the power conversion efficiency (PCE) of PbS CQD solar cells increases year by year, the stability of its devices has always attracted much attention. The existing technology has significantly improved the air stability of PbS CQD solar cells by successfully designing the device structure of ITO / zinc oxide (ZnO) / iodine encapsulated PbS CQD / ethylenedithiol (EDT) encapsulated PbS CQD / gold (see reference: Nat. Mater. 2014, 13, 796). Subsequently, almost all PbS CQD solar cells adopted this efficient NIP device structure. Recently, P-type organic polymers have been used to replace PbS-EDT as a new hole transport layer (HTL) to further improve the hole extraction ability (see reference: Nat. Energy 2019, 4, 969, Adv. Mater. 2020, 32, 2004985, Adv. Energy Mater. 2021, 12, 2102689). These organic polymers are compatible with large-area single-film processing and are expected to become the next generation of more efficient hole transport layer materials for CQD solar cells.
[0004] Although the excellent air stability of quantum dot solar cells has been emphasized in a large number of literatures, the operational stability, which is more critical for practical applications, has received limited attention. In the widely adopted NIP device structure, the stability of the hole transport layer directly exposed to the external environment has a great impact on the stability of the device. The currently commonly used PbS-EDT hole transport layer is easily oxidized under light conditions, resulting in a decrease in device performance. Currently, for PbS CQD solar cells based on organic HTL, the maximum power point (MPP) T of the most stable device reported is 2.5 ~ 1.5 W. 90 (The time it takes for the device efficiency to decay to 90% of the initial value) is 120 hours (see reference: Adv. Energy Mater. 2021, 12, 2102689), while in inorganic HTL-based devices, the optimal T 90 The time taken for the device to be exposed to light is 260 hours (see reference: Solar RRL 2022, 6, 2200488), which greatly hinders the practical application of the device. More and more studies have shown that the interface has a significant impact on the performance and stability of optoelectronic devices, especially in lead sulfide quantum dot optoelectronic devices. This problem needs to be further solved. Summary of the invention
[0005] The present invention aims at the shortcomings of the prior art lead sulfide quantum dot optoelectronic device in terms of interface contact and low working stability, and provides a lead sulfide quantum dot optoelectronic device structure and a preparation method thereof which can effectively improve efficiency and working stability.
[0006] The technical solution for achieving the purpose of the present invention is to provide a lead sulfide quantum dot photoelectric device, which includes a conductive glass substrate, an electron transport layer, a quantum dot active layer, a hole transport layer and an electrode; the hole transport layer is a hole transport modification layer with a three-layer structure, including a lower interface modification layer, a P-type organic polymer layer and an upper interface modification layer: the lower interface modification layer is a lead sulfide quantum dot film of thiol small molecule ligands formed on the lower surface of the P-type organic polymer layer, the size of the quantum dots is 3 to 10 nanometers, and the film thickness is 3 to 20 nanometers; the upper interface modification layer is a tris-pentafluorophenyl boron-doped poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] film formed on the upper surface of the P-type organic polymer layer, the mass ratio of tris-pentafluorophenyl boron to poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] is 1:20 to 1:4, and the film thickness is 5 to 30 nanometers.
[0007] The quantum dot active layer of the present invention is a lead sulfide quantum dot film with a thickness of 100 to 800 nanometers; the size of the lead sulfide quantum dots is 3 to 10 nanometers; and the electron transport layer is one of SnO2 or ZnO films with a thickness of 10 to 200 nanometers.
[0008] The P-type organic polymer layer described in the present invention is one of poly (3-hexylthiophene-2,5-diyl), P5TCN-2F, P5TCN-F25, PBDB-T, and PM6 thin films; in the upper interface modification layer, the mass ratio of trispentafluorophenylboron:poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] is 1:10 to 1:4.
[0009] The photoelectric device described in the present invention includes a solar cell, an LED device and a photodetector.
[0010] The technical solution of the present invention also includes a method for preparing a lead sulfide quantum dot photoelectric device, the steps of which are as follows: (1) Spin coating an electron transport material on a conductive glass substrate to obtain an electron transport layer; (2) Preparing a lead sulfide quantum dot active layer on the electron transport layer; (3) preparing a three-layer hole transport modification layer, including a lower interface modification layer, a P-type organic polymer layer, and an upper interface modification layer; (a) preparing a lower interface modification layer: spin coating lead sulfide quantum dots wrapped with oleic acid on the quantum dot active layer and performing solid-state ligand exchange, wherein the size of the quantum dots is 3 to 10 nanometers, to obtain a lower interface modification layer having a film thickness of 3 to 20 nanometers; (b) preparing a P-type organic polymer layer: spin coating a P-type organic polymer solution on the lower interface modification layer to obtain a P-type organic polymer film, and then annealing the film at a temperature of 30° C. to 70° C. for 1 to 10 minutes to obtain a P-type organic polymer layer with a film thickness of 10 to 200 nanometers; (c) preparing an upper interface modification layer: spreading tripentafluorophenylboron-doped poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] on the upper surface of the annealed P-type organic polymer layer in a mass ratio of tripentafluorophenylboron to poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] of 1:20 to 1:4, and spin-drying to obtain an upper interface modification layer with a film thickness of 5 to 30 nanometers; (4) Vapor-depositing a gold electrode on the upper interface modification layer of the hole transport modification layer prepared in step (3) to obtain a lead sulfide quantum dot optoelectronic device.
[0011] The preparation of the lower interface modification layer of the present invention comprises the following steps: dissolving oleic acid-wrapped lead sulfide quantum dots in a non-polar solvent, and spin-coating the obtained solution on a quantum dot active layer to form a quantum dot film, wherein the non-polar solvent comprises one of n-hexane or n-octane; diluting thiol small molecules in the solvent at a volume ratio of 1:10000 to 1:10, covering the surface of the quantum dot film for solid-state ligand exchange, and then washing and spin-drying to obtain the lower interface modification layer; the thiol small molecules comprise one of EDT or MPA, and the solvent comprises one of methanol or isopropanol.
[0012] The principle of the present invention is to introduce a lead sulfide quantum dot layer exchanged with thiol molecules at the lower interface of the P-type organic polymer layer and a poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] layer doped with trispentafluorophenylboron at the upper interface to perform double interface treatment. Taking the poly(3-hexylthiophene-2,5-diyl) hole transport layer as an example, the efficiency is very low without an interface layer. After the interface layer is introduced, on the one hand, the lower interface layer can serve as an effective transition layer between the all-inorganic halogen passivated PbS quantum dot active layer and the organic polymer, and on the other hand, tris-pentafluorophenylborane-doped poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] helps to form a stable ohmic contact between poly(3-hexylthiophene-2,5-diyl) and the gold electrode, reducing the potential barrier between poly(3-hexylthiophene-2,5-diyl) and the gold electrode; at the same time, doping improves the mobility of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], accelerates carrier transport, and can effectively block water and oxygen, preventing quantum dots from being over-oxidized, further improving the working stability of lead sulfide quantum dot optoelectronic devices. The double interface layer achieves good contact by promoting surface energy conversion between different layers.
[0013] Compared with the prior art, the technical solution provided by the present invention has the following advantages: 1. The optoelectronic device provided by the present invention has a hole transport layer that adopts a three-layer hole transport modification layer. The three layers work together to achieve excellent extraction and transmission of holes from the quantum dot active layer to the gold electrode, and trispentafluorophenylborane-doped poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] not only effectively blocks water and oxygen, but also can construct stable ohmic contacts between various P-type organic polymers and the gold electrode.
[0014] 2. The present invention provides a lead sulfide quantum dot optoelectronic device structure with a double interface layer, which realizes stable ohmic contact between a variety of organic polymers and gold electrodes; unlike the generally expensive and difficult to synthesize polymers, poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] as a typical commercial organic polymer material has high cost-effectiveness and is expected to be used in large-scale manufacturing.
[0015] 3. The surface treatment process provided by the present invention has wide applicability and is applicable to a variety of P-type organic polymer hole transport layers; through this process treatment, both device efficiency and working stability are improved.
[0016] 4. The technical solution provided by the present invention relates to the technical field of photoelectric device preparation, and can be applied not only to lead sulfide quantum dot solar cells, but also can be widely applied to lead sulfide quantum dot LED devices, photodetectors, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A schematic diagram of the structure of a lead sulfide quantum dot photovoltaic device solar cell provided by the present invention; Figure 1 In the figure, 1. Conductive glass substrate; 2. Electron transport layer; 3. Lead sulfide active layer; 4. Hole transport modification layer; 5. Gold electrode; Figure 2 A schematic diagram of the structure of a hole transport modification layer provided in an embodiment of the present invention; Figure 2 In, 4-1. Lower interface modification layer; 4-2. P-type organic polymer layer; 4-3. Upper interface modification layer; Figure 3 This is a scanning electron microscope image of the interface of the lead sulfide quantum dot solar cell prepared in Example 1 of the present invention; Figure 4 A line graph showing the solution concentration and device efficiency of the lead sulfide quantum dot solar cell prepared in Example 1 of the present invention corresponding to poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]; Figure 5 This is a current density-voltage (JV) curve of the lead sulfide quantum dot solar cell prepared in Example 1 of the present invention; Figure 6 This is a graph showing the air operation stability of the lead sulfide quantum dot solar cell prepared in Example 1 of the present invention under continuous illumination conditions; Figure 7 This is a current density-voltage (JV) curve of the lead sulfide quantum dot solar cell prepared in Example 2 of the present invention; Figure 8 This is a current density-voltage (JV) curve of the lead sulfide quantum dot solar cell prepared in Example 3 of the present invention; Fig. 9 This is a current density-voltage (JV) curve of the lead sulfide quantum dot solar cell prepared in Example 4 of the present invention; Fig.10 This is a current density-voltage (JV) curve of the lead sulfide quantum dot solar cell prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments. Example 1
[0019] This embodiment provides a lead sulfide quantum dot optoelectronic device, taking a solar cell as an example.
[0020] See attached Figure 1 , 2 , are schematic diagrams of the structures of the lead sulfide quantum dot solar cell and the hole transport modification layer provided in this embodiment; Figure 1 The device structure shown is: an electron transport layer 2, a lead sulfide quantum dot active layer 3, a hole transport modification layer 4 and a gold electrode 5 are sequentially prepared on a conductive glass substrate 1; Figure 2 The hole transport modification layer structure shown is: an upper interface modification layer 4-3 and a lower interface modification layer 4-1 formed on the upper and lower surfaces of a P-type organic polymer layer 4-2, respectively.
[0021] This embodiment provides a lead sulfide quantum dot solar cell, and the specific steps of preparation are as follows: Step 1: Spin-coat a ZnO film with a thickness of about 80 nanometers on a clean indium tin oxide (ITO) conductive glass substrate to obtain an electron transport layer; Step 2: In a nitrogen glove box, on the basis of the electron transport layer, a lead sulfide quantum dot solution is spin-coated at 2000 rpm for 15 seconds to obtain a lead sulfide quantum dot light absorption layer with a thickness of about 400 nanometers, and then annealed at 70° C. for 10 minutes.
[0022] Step 3: prepare the lower interface layer of lead sulfide quantum dots with MPA ligands on the lead sulfide quantum dot light absorbing layer. The specific method is: dissolve the lead sulfide quantum dots wrapped with oleic acid in n-octane to prepare a solution with a concentration of 5 mg / ml, spin-coat at a speed of 2500 rpm for 20 seconds to form a quantum dot film with a thickness of about 7 nanometers. Then soak it in a methanol solution of MPA (volume ratio of 1:500) for 30 seconds, wash it with methanol and spin dry it to obtain the lower interface layer.
[0023] Step 4: Prepare a P-type organic polymer layer by spin coating on the lower interface layer. The specific method is: dissolve poly (3-hexylthiophene-2,5-diyl) in chlorobenzene to prepare a solution with a concentration of 6 mg / ml, spin coat at 3000 rpm for 20 seconds to form a P-type organic polymer film with a thickness of about 20 nanometers, and anneal at 50°C for 5 minutes to obtain a P-type organic polymer layer.
[0024] Step 5: Spin coating the P-type organic polymer layer to prepare an upper interface layer. The specific method is: dissolve poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] in toluene to prepare a solution with a concentration of 3 mg per milliliter, dope with 15% mass fraction of trispentafluorophenyl borane, spin coat at a rotation speed of 3000 revolutions per minute for 40 seconds to form a thin film with a thickness of about 8 nanometers to obtain the upper interface layer.
[0025] Step six, vacuum thermally evaporate a gold electrode with a thickness of 80 nanometers on the upper interface layer to obtain a lead sulfide quantum dot solar cell.
[0026] See attached Figure 3 , which is a scanning electron microscope image of the lead sulfide quantum dot solar cell interface provided in this embodiment.
[0027] According to the technical scheme of this embodiment, the poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] in step 5 is dissolved in toluene at concentrations of 1, 2, 4 and 5 mg / ml, respectively, to prepare a lead sulfide quantum dot solar cell.
[0028] See attached Figure 4 , which is a line graph of the lead sulfide quantum dot solar cell prepared in this embodiment corresponding to different poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] solution concentrations and device efficiency, Figure 4 It can be seen that the optimal concentration is 3 mg per ml.
[0029] See attached Figure 5 , which is a current density-voltage (JV) curve of a lead sulfide quantum dot solar cell provided in this embodiment using lead sulfide quantum dots as a light absorption layer, lead sulfide with MPA ligand as a lower interface modification layer, poly (3-hexylthiophene-2,5-diyl) as a hole transport layer, and poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] as an upper interface modification layer; at AM 1.5G, 100 mW / cm 2 Under standard test conditions, the short-circuit current density of the device was measured to be 29.45 mA / cm 2 , the open circuit voltage is 0.67 V, the fill factor is 71.77%, and the photoelectric conversion efficiency is 14.16%.
[0030] See attached Figure 6 , which is a graph showing the operating stability of the lead sulfide quantum dot solar cell provided in this embodiment under continuous illumination of AM1.5G in the air. The air humidity is about 45%, the device surface temperature is about 50°C, and after about 520 hours, the efficiency of the unpackaged device can still maintain 90% of the original efficiency. Example 2
[0031] This embodiment provides a lead sulfide quantum dot solar cell, the structure of which is as shown in the attached figure. Figure 1 and attached Figure 2 As shown, the battery preparation includes the following steps: an electron transport layer, a lead sulfide quantum dot light absorption layer, a lower interface layer, a P-type organic polymer layer, an upper interface layer and a gold electrode are sequentially prepared on a conductive glass substrate. The specific steps of preparation are as follows: Step 1: Spin-coat a ZnO film with a thickness of about 80 nanometers on a clean indium tin oxide (ITO) conductive glass substrate to obtain an electron transport layer; Step 2: In a nitrogen glove box, on the basis of the electron transport layer, a lead sulfide quantum dot solution is spin-coated at 2000 rpm for 15 seconds to obtain a lead sulfide quantum dot light absorption layer with a thickness of about 400 nanometers, and then annealed at 70° C. for 10 minutes.
[0032] Step 3: prepare the lower interface layer of lead sulfide quantum dots with MPA ligands on the lead sulfide quantum dot light absorbing layer. The specific method is: dissolve the lead sulfide quantum dots wrapped with oleic acid in n-octane to prepare a solution with a concentration of 5 mg / ml, spin-coat at a speed of 2500 rpm for 20 seconds to form a quantum dot layer with a thickness of about 7 nanometers. Then soak it in a methanol solution of MPA (volume ratio of 1:500) for 30 seconds, wash it with methanol and spin dry it to obtain the lower interface layer.
[0033] Step 4: Spin-coat a P-type organic polymer layer on the lower interface layer. The specific method is: dissolve P5TCN-2F in chlorobenzene to prepare a solution with a concentration of 6 mg / ml, spin-coat at 3000 rpm for 20 seconds to form a P-type organic polymer layer with a thickness of about 20 nanometers, and anneal at 50°C for 5 minutes.
[0034] Step 5, spin coating an upper interface layer on the P-type organic polymer layer. The specific method is: dissolve poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] in toluene to prepare a solution with a concentration of 3 mg per milliliter, dope with 15% mass fraction of trispentafluorophenyl borane, spin coat at a rotation speed of 3000 revolutions per minute for 40 seconds to form an upper interface layer with a thickness of about 8 nanometers.
[0035] Step six, vacuum thermally evaporate a gold electrode with a thickness of 80 nanometers on the upper interface layer to obtain a lead sulfide quantum dot solar cell.
[0036] See attached Figure 7 , which is a current density-voltage (JV) curve of a lead sulfide quantum dot solar cell provided in this embodiment using lead sulfide quantum dots as a light absorption layer, lead sulfide with MPA ligand as a lower interface modification layer, P5TCN-2F as a P-type organic polymer layer, and poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] as an upper interface modification layer; at AM1.5G, 100 mW / cm2 Under standard test conditions, the short-circuit current density of the device was measured to be 27.19 mA / cm 2 , the open circuit voltage is 0.67 V, the fill factor is 68.64%, and the photoelectric conversion efficiency is 12.50%. Example 3
[0037] This embodiment provides a lead sulfide quantum dot solar cell, the structure of which is as shown in the attached figure. Figure 1 and attached Figure 2 As shown, the battery preparation includes the following steps: an electron transport layer, a lead sulfide quantum dot light absorption layer, a lower interface layer, a P-type organic polymer layer, an upper interface layer and a gold electrode are sequentially prepared on a conductive glass substrate. The specific steps of preparation are as follows: Step 1: Spin-coat a ZnO film with a thickness of about 80 nanometers on a clean indium tin oxide (ITO) conductive glass substrate to obtain an electron transport layer; Step 2: In a nitrogen glove box, on the basis of the electron transport layer, a lead sulfide quantum dot solution is spin-coated at 2000 rpm for 15 seconds to obtain a lead sulfide quantum dot light absorption layer with a thickness of about 400 nanometers, and then annealed at 70° C. for 10 minutes.
[0038] Step 3: prepare the lower interface layer of lead sulfide quantum dots with MPA ligands on the lead sulfide quantum dot light absorbing layer. The specific method is: dissolve the lead sulfide quantum dots wrapped with oleic acid in n-octane to prepare a solution with a concentration of 5 mg / ml, spin-coat at a speed of 2500 rpm for 20 seconds to form a quantum dot layer with a thickness of about 7 nanometers. Then soak it in a methanol solution of MPA (volume ratio of 1:500) for 30 seconds, wash it with methanol and spin dry it to obtain the lower interface layer.
[0039] Step 4: Spin-coat a P-type organic polymer layer on the lower interface layer. The specific method is: dissolve P5TCN-F25 in chlorobenzene to prepare a solution with a concentration of 6 mg / ml, spin-coat at 3000 rpm for 20 seconds to form a P-type organic polymer layer with a thickness of about 20 nanometers, and anneal at 50°C for 5 minutes.
[0040] Step 5, spin coating an upper interface layer on the P-type organic polymer layer. The specific method is: dissolve poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] in toluene to prepare a solution with a concentration of 3 mg per milliliter, dope with 15% mass fraction of trispentafluorophenyl borane, spin coat at a rotation speed of 3000 revolutions per minute for 40 seconds to form an upper interface layer with a thickness of about 8 nanometers.
[0041] Step six, vacuum thermally evaporate a gold electrode with a thickness of 80 nanometers on the upper interface layer to obtain a lead sulfide quantum dot solar cell.
[0042] See attached Figure 8, which is a current density-voltage (JV) curve of a lead sulfide quantum dot solar cell provided in this embodiment using lead sulfide quantum dots as a light absorption layer, lead sulfide with MPA ligand as a lower interface modification layer, P5TCN-F25 as a P-type organic polymer layer, and poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] as an upper interface modification layer; at AM1.5G, 100 mW / cm 2 Under standard test conditions, the short-circuit current density of the device was measured to be 27.10 mA / cm 2 , the open circuit voltage is 0.67 V, the fill factor is 69.24%, and the photoelectric conversion efficiency is 12.57%. Example 4
[0043] This embodiment provides a lead sulfide quantum dot solar cell, the structure of which is as shown in the attached figure. Figure 1 and attached Figure 2 As shown, the battery preparation includes the following steps: an electron transport layer, a lead sulfide quantum dot light absorption layer, a lower interface layer, a P-type organic polymer layer, an upper interface layer and a gold electrode are sequentially prepared on a conductive glass substrate. The specific steps of preparation are as follows: Step 1: Spin-coat a ZnO film with a thickness of about 80 nanometers on a clean indium tin oxide (ITO) conductive glass substrate to obtain an electron transport layer; Step 2: In a nitrogen glove box, on the basis of the electron transport layer, a lead sulfide quantum dot solution is spin-coated at 2000 rpm for 15 seconds to obtain a lead sulfide quantum dot light absorption layer with a thickness of about 400 nanometers, and then annealed at 70° C. for 10 minutes.
[0044] Step 3: prepare the lower interface layer of lead sulfide quantum dots with MPA ligands on the lead sulfide quantum dot light absorbing layer. The specific method is: dissolve the lead sulfide quantum dots wrapped with oleic acid in n-octane to prepare a solution with a concentration of 5 mg / ml, spin-coat at a speed of 2500 rpm for 20 seconds to form a quantum dot layer with a thickness of about 7 nanometers. Then soak it in a methanol solution of MPA (volume ratio of 1:500) for 30 seconds, wash it with methanol and spin dry it to obtain the lower interface layer.
[0045] Step 4: Spin-coat a P-type organic polymer layer on the lower interface layer. The specific method is: dissolve PBDB-T in chlorobenzene to prepare a solution with a concentration of 6 mg / ml, spin-coat at 3000 rpm for 20 seconds to form a P-type organic polymer layer with a thickness of about 20 nanometers, and anneal at 50°C for 5 minutes.
[0046] Step 5, spin coating an upper interface layer on the P-type organic polymer layer. The specific method is: dissolve poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] in toluene to prepare a solution with a concentration of 3 mg per milliliter, dope with 15% mass fraction of trispentafluorophenyl borane, spin coat at a rotation speed of 3000 revolutions per minute for 40 seconds to form an upper interface layer with a thickness of about 8 nanometers.
[0047] Step six, vacuum thermally evaporate a gold electrode with a thickness of 80 nanometers on the upper interface layer to obtain a lead sulfide quantum dot solar cell.
[0048] See attached Fig. 9 , which is a current density-voltage (JV) curve of a lead sulfide quantum dot solar cell provided in this embodiment using lead sulfide quantum dots as a light absorption layer, lead sulfide with MPA ligand as a lower interface modification layer, PBDB-T as a P-type organic polymer layer, and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] as an upper interface modification layer; at AM1.5G, 100 mW / cm 2 Under standard test conditions, the short-circuit current density of the device was measured to be 26.53 mA / cm 2 , the open circuit voltage is 0.68 V, the fill factor is 65.70%, and the photoelectric conversion efficiency is 11.85%. Example 5
[0049] This embodiment provides a lead sulfide quantum dot solar cell, the structure of which is as shown in the attached figure. Figure 1 and attached Figure 2 As shown, the battery preparation includes the following steps: an electron transport layer, a lead sulfide quantum dot light absorption layer, a lower interface layer, a P-type organic polymer layer, an upper interface layer and a gold electrode are sequentially prepared on a conductive glass substrate. The specific steps of preparation are as follows: Step 1: Spin-coat a ZnO film with a thickness of about 80 nanometers on a clean indium tin oxide (ITO) conductive glass substrate to obtain an electron transport layer; Step 2: In a nitrogen glove box, on the basis of the electron transport layer, a lead sulfide quantum dot solution is spin-coated at 2000 rpm for 15 seconds to obtain a lead sulfide quantum dot light absorption layer with a thickness of about 400 nanometers, and then annealed at 70° C. for 10 minutes.
[0050] Step 3: prepare the lower interface layer of lead sulfide quantum dots with MPA ligands on the lead sulfide quantum dot light absorbing layer. The specific method is: dissolve the lead sulfide quantum dots wrapped with oleic acid in n-octane to prepare a solution with a concentration of 5 mg / ml, spin-coat at a speed of 2500 rpm for 20 seconds to form a quantum dot layer with a thickness of about 7 nanometers. Then soak it in a methanol solution of MPA (volume ratio of 1:500) for 30 seconds, wash it with methanol and spin dry it to obtain the lower interface layer.
[0051] Step 4: Spin-coat a P-type organic polymer layer on the lower interface layer. The specific method is: dissolve PM6 in chlorobenzene to prepare a solution with a concentration of 6 mg / ml, spin-coat at 3000 rpm for 20 seconds to form a P-type organic polymer layer with a thickness of about 20 nanometers, and anneal at 50°C for 5 minutes.
[0052] Step 5, spin coating an upper interface layer on the P-type organic polymer layer. The specific method is: dissolve poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] in toluene to prepare a solution with a concentration of 3 mg per milliliter, dope with 15% mass fraction of trispentafluorophenyl borane, spin coat at a rotation speed of 3000 revolutions per minute for 40 seconds to form an upper interface layer with a thickness of about 8 nanometers.
[0053] Step six, vacuum thermally evaporate a gold electrode with a thickness of 80 nanometers on the upper interface layer to obtain a lead sulfide quantum dot solar cell.
[0054] See attached Fig.10 , which is a current density-voltage (JV) curve of a lead sulfide quantum dot solar cell provided in this embodiment using lead sulfide quantum dots as a light absorption layer, lead sulfide with MPA ligand as a lower interface modification layer, PM6 as a P-type organic polymer layer, and poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] as an upper interface modification layer; at AM 1.5G, 100 mW / cm 2 Under standard test conditions, the short-circuit current density of the device was measured to be 25.27 mA / cm 2 , the open circuit voltage is 0.69 V, the fill factor is 58.26%, and the photoelectric conversion efficiency is 10.16%.
Claims
1. A lead sulfide quantum dot optoelectronic device, comprising a conductive glass substrate, an electron transport layer, a quantum dot active layer, a hole transport layer and an electrode, characterized in that: The hole transport layer is a three-layer hole transport modification layer, including a lower interface modification layer, a P-type organic polymer layer, and an upper interface modification layer: the lower interface modification layer is a lead sulfide quantum dot film of thiol small molecule ligands formed on the lower surface of the P-type organic polymer layer, the size of the quantum dots is 3 to 10 nanometers, and the film thickness is 3 to 20 nanometers; the upper interface modification layer is a tris-pentafluorophenyl boron-doped poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] film formed on the upper surface of the P-type organic polymer layer, the mass ratio of tris-pentafluorophenyl boron to poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] is 1:20 to 1:4, and the film thickness is 5 to 30 nanometers.
2. A lead sulfide quantum dot optoelectronic device according to claim 1, characterized in that: In the upper interface modification layer, the mass ratio of trispentafluorophenylboron to poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] is 1:10 to 1:
4.
3. A lead sulfide quantum dot optoelectronic device according to claim 1, characterized in that: The P-type organic polymer layer is one of poly (3-hexylthiophene-2,5-diyl), P5TCN-2F, P5TCN-F25, PBDB-T, and PM6 thin films.
4. A lead sulfide quantum dot optoelectronic device according to claim 1, characterized in that: The quantum dot active layer is a lead sulfide quantum dot film with a thickness of 100 to 800 nanometers; the size of the lead sulfide quantum dots is 3 to 10 nanometers.
5. A lead sulfide quantum dot optoelectronic device according to claim 1, characterized in that: The electron transport layer is one of SnO2 or ZnO thin films with a thickness of 10 to 200 nanometers.
6. A lead sulfide quantum dot optoelectronic device according to claim 1, characterized in that: The photoelectric devices include solar cells, LED devices and photodetectors.
7. A method for preparing a lead sulfide quantum dot optoelectronic device according to claim 1, characterized in that The steps include: (1) Spin coating an electron transport material on a conductive glass substrate to obtain an electron transport layer; (2) Preparing a lead sulfide quantum dot active layer on the electron transport layer; (3) preparing a three-layer hole transport modification layer, including a lower interface modification layer, a P-type organic polymer layer, and an upper interface modification layer; (a) preparing a lower interface modification layer: spin coating lead sulfide quantum dots wrapped with oleic acid on the quantum dot active layer and performing solid-state ligand exchange, wherein the size of the quantum dots is 3 to 10 nanometers, to obtain a lower interface modification layer having a film thickness of 3 to 20 nanometers; (b) preparing a P-type organic polymer layer: spin coating a P-type organic polymer solution on the lower interface modification layer to obtain a P-type organic polymer film, and then annealing the film at a temperature of 30° C. to 70° C. for 1 to 10 minutes to obtain a P-type organic polymer layer with a film thickness of 10 to 200 nanometers; (c) preparing an upper interface modification layer: spreading tripentafluorophenylboron-doped poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] on the upper surface of the annealed P-type organic polymer layer in a mass ratio of tripentafluorophenylboron to poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] of 1:20 to 1:4, and spin-drying to obtain an upper interface modification layer with a film thickness of 5 to 30 nanometers; (4) Vapor-depositing a gold electrode on the upper interface modification layer of the hole transport modification layer prepared in step (3) to obtain a lead sulfide quantum dot optoelectronic device.
8. The method for preparing a lead sulfide quantum dot optoelectronic device according to claim 7, characterized in that: The preparation of the lower interface modification layer comprises the following steps: dissolving oleic acid-wrapped lead sulfide quantum dots in a non-polar solvent, and spin-coating the obtained solution on a quantum dot active layer to form a quantum dot film, wherein the non-polar solvent comprises one of n-hexane or n-octane; diluting thiol small molecules in the solvent at a volume ratio of 1:10000 to 1:10, covering the surface of the quantum dot film for solid-state ligand exchange, and then washing and spin-drying to obtain the lower interface modification layer; the thiol small molecules comprise one of EDT or MPA, and the solvent comprises one of methanol or isopropanol.
Citation Information
Patent Citations
Method for improving performance of electroluminescent device by modifying indium phosphide quantum dots on interface of thiol compound
CN114242923A
Indenofluorene conjugated small organic molecule hole transport material as well as preparation method and application thereof
CN117551105A
PbS quantum dot film photoelectric detector and preparation method thereof
CN118301950A
Quantum dot, ink composition, and printed matter
JP2020106820A
Inorganic light emitting diode and inorganic light emitting device including the same
US20210167321A1
Cited By
Lead sulfide quantum dot based on micro-emulsion nano-reactor, lead sulfide quantum dot film, multi-layer partitioned wide-spectrum photoelectric detector and preparation method of multi-layer partitioned wide-spectrum photoelectric detector
CN122501906A